The Effect of Ultrasound-Measured Preinduction Cervical Length on Delivery Outcome in a Low-Resource Setting - Chidebe C. Anikwe; Bartholomew C. Okorochukwu; Emmanuel Uchendu; Cyril C. Ikeoha (The Scientific World Journal)
Background. Induction of labour is not without risk, and it calls for a method that will be sensitive enough to predict successful labour induction. Aim. This study aims to evaluate the role of transvaginal ultrasonographic cervical length measurement at term in the prediction of successful induction of labour (IOL). Materials and Methods. This prospective study was carried out in the Department of Obstetrics and Gynaecology of Federal Teaching Hospital Abakaliki between 1st of July and 30th of November 2015. Preinduction Bishop score and cervical length were assessed before induction of labour. Intracervical, cervical, extraamniotic Foley catheter was used to improve the Bishop score. The data were analyzed using the IBM SPSS Statistics 20. Results. The mean maternal age of the study group was 30.68 ± 6.38 years with a range of 19–43 years. The mean gestational age and parity were 39.57 ± 1.49 and 1.85 ± 0.63, respectively. All the women studied had successful induction of labour with mean induction delivery time of 8.1 ± 3.0 hours and mean duration of labour of 7.4 ± 2.9 hours. Preinduction cervical length is a good predictor of a short duration of labour (P=0.001). Parturient with a preinduction cervical length of less than 3 cm was likely to have labour lasting less than 6 hours (RR = 4.20 (95% CI 1.85–9.529). Conclusion. Transvaginal sonographic measurement of cervical length provides a useful prediction of the likelihood of duration of labour following the induction of labour. It is recommended that IOL should be considered and success anticipated in a parturient with a cervical length less than 3 cm.